Performance and Emissions Investigation of Methanol-Butanol-Ethanol Accumulation as an Alternative Gasoline Mixture in Spark Ignition Engines - Setyono, Gatot; Khusna, Dwi; Kholili, Navik; Diantoro, Nova Arizal; Saputra, Firman Dirga (Mechanical Engineering Department - Institut Teknologi Adhi Tama Surabaya, 2024)
Alternative fuels such as Methanol-Butanol-Etanol (MBE) are worthy of development because of their optimal characteristics in SI engines. Selective government regulations on vehicle emissions require a shift to environmentally friendly innovative energy. Fuel-containing alcohol has been proven to reduce pollution levels in vehicles optimally. This research has explored MBE fuel mixtures with three variants through experimental methods. Variations MBE1, MBE2 and MBE3 were mixed with gasoline (RON-90) with capacities (5:2:1, 8:4:1, and 10:6:1)v/v when tested using a dyno test on an SI engine automatic type compression ratio 10:1 with a speed gap of 4000-9000rpm. During testing, torque and Mep experienced an optimal increase in MBE3 fuel of 10.78% and 10.55% compared to commercial fuel (RON-90). Engine power and thermal efficiency increased respectively by 10.03% and 10.69%. This condition is inversely proportional to SFC, which decreased by 21.05%. Furthermore, CO and HC exhaust emissions decreased by 12.12% and 4.60% respectively. This phenomenon shows that MBE fuel shows environmentally friendly performance and exhaust emissions for SI engines in daily activities.